POP - Mauler, Sandra; Waldhart, Elisabeth; Bonz, Jochen (bricolage, 2019)
POP - with this motto, the present volume reaches out to a dazzling dimension of everyday culture and approaches it in a series of detailed studies. Subjects include the goa techno scene, Internet memes, fan fiction, Game of Thrones, dumpster diving, and veganism. The contributions are by students and are based on undergraduate papers that emerged from a two-semester seminar that combined an introduction to the concepts of British cultural studies with an ethnographic fieldwork exercise. A methodological paper by J. Bonz on ethnographic fieldwork, which also emerged from the seminar, complements the studies. The student articles are framed by three contributions from renowned popular culture researchers: S. Egger writes about Beyoncé Knowles from the point of view of aesthetic social critique, C. Bareither about communalizing emotional practices, and M. Tauschek gives an overview of popular culture research in the discourse of European Ethnology in conversation with S. Mauler. As a special extra, the volume includes a stretch of 29 photographs by B. Ludewig on the topic of contemporary avant-garde festivals.